Exploring biodiversity patterns amongst southern Gondwana’s primeval forests: taxonomy of lycopod and progymnosperm fossils from the Upper Devonian Witpoort Formation (Witteberg Group, South Africa) - Harris, Christopher (My University, 2020)
Famennian-aged fossil localities Waterloo Farm and Coombs Hill from the Witpoort Formation (Witteberg Group, Eastern Cape, South Africa) provide unprecedentedly complete Late Devonian plant remains from southern Gondwana, evidencing rich and diverse floras in a high palaeo-latitude setting. These localities present the earliest evidence of high latitude trees. Occurrence of one or more rhizomorphic lycopods together with Archaeopteris at the two Witpoort Formation localities suggests an ecological association like that observed across much of Laurussia during the Famennian. With description of four new lycopod species it is shown that of three lycopod species identified at each locality, none occur at both. The only species currently recognised at both localities is Archaeopteris notosaria. New lycopod species include the youngest records of Colpodexylon Banks, a fertile archaeosigillariid (suggesting inclusion of the family in Protolepidodendrales) and a likely heterosporous form. It is here proposed that protolepidodendralean lycopods persisted at high-latitudes until at least the Upper Famennian (late, Late Devonian), whilst in the tropics its members were replaced by advanced, opportunistic or pioneering taxa around the Middle-Late Devonian boundary. New Coombs Hill derived specimens of Archaeopteris notosaria (originally described from Waterloo Farm), allow diagnosis of additional vegetative and fertile characters for the species, permitting re-interpretation of the holotype, as well as detailed comparisons with worldwide records of the genus
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science, 2020